2021
DOI: 10.3389/fonc.2021.797194
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Outcome for ETV6/RUNX1-Positive Pediatric Acute Lymphoblastic Leukemia: A Report From the South China Children’s Leukemia Group

Abstract: PurposeTo analyzed the outcome of ETV6/RUNX1-positive pediatric acute B lymphoblastic leukemia (B-ALL) with the aim of identifying prognostic value.MethodA total of 2,530 pediatric patients who were diagnosed with B-ALL were classified into two groups based on the ETV6/RUNX1 status by using a retrospective cohort study method from February 28, 2008, to June 30, 2020, at 22 participating ALL centers.ResultsIn total, 461 (18.2%) cases were ETV6/RUNX1-positive. The proportion of patients with risk factors (age &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…2. Actually, the incidence of BCR-ABL1 positive ALL in this study was close to another report from the South China Children’s Leukemia Group ( 27 ), suggesting that the positive rate of BCR-ABL1 in the population of South China may just be higher than that in the regions involved in other protocols. In addition, the incidence of induction failure (IF) was higher than that reported in other protocols ( 28 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2. Actually, the incidence of BCR-ABL1 positive ALL in this study was close to another report from the South China Children’s Leukemia Group ( 27 ), suggesting that the positive rate of BCR-ABL1 in the population of South China may just be higher than that in the regions involved in other protocols. In addition, the incidence of induction failure (IF) was higher than that reported in other protocols ( 28 ).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, research in recent years have shown that patients with central nervous system leukemia (CNSL), T-cell immunophenotype, low hypodiploid, BCR-ABL1 positive, E2A-PBX1/TCF3-PBX1 positive, or MLL rearrangements also had a poor prognosis ( 14 17 ). Conversely, patients with ETV6-RUNX1/TEL-AML1 positive had a better prognosis ( 27 , 40 ). In the present study, we found that T-cell immunophenotype was a risk factor for EFS, while ETV6-RUNX1/TEL-AML1 was a protective factor, which were agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The South China Children’s Leukemia Group (SCCLG)-ALL-2016 is a prospective, multi-institutional clinical trial involving 18 major hospitals/medical centers ( 9 , 10 ). We designed the SCCLG-ALL-2016 collaborative protocol based on the backbones of Berlin-Frankfurt-Münster (BFM) ALL-IC-2009 and Guangdong (GD)-2008-ALL ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various chromosomal alterations in ALL are important in driving chromosomal gains and losses that may be associated with the target therapy, survival and relapse of the disease ( 5 , 11 , 12 ). Chromosomal abnormalities such as t (4;11) (q21;q23) are associated with poor prognosis ( 13 , 14 ), whereas patients with t(12;21)(p13;q22) translocation have a better survival rate ( 15 , 16 ). A subtype of ALL carrying t(9;22)(q34;q11.2) translocation had a poor prognosis, which has been improved significantly by the combination of tyrosine kinase and chemotherapy strategies ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%